Laporan Observasi Sosial Emosional pada Anak Usia Dini di TK An-Nida - Maldina Aulia Rahmi; Khadijah Khadijah (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to describe the socio-emotional development of early childhood students at TK An-Nida and explore the involvement of parents and teachers in supporting the process. A descriptive qualitative method was used, involving direct observation and interviews. The results show that most children are at the "developing as expected" stage in terms of self-awareness, motivation, empathy, social skills, and self-regulation. However, challenges remain in emotional regulation and limited parental involvement in social-emotional learning activities at school. The study highlights the importance of synergy between school and family in creating an environment that supports optimal socio-emotional development in early childhood.